Prolactin stimulates the L-type calcium channel-mediated transepithelial calcium transport in the duodenum of male rats - Nitita Dorkkam (2018)
Elevated plasma levels of prolactin (PRL) have been reported in several physiological and pathological conditions, such as lactation, prolactinoma, and dopaminergic antipsychotic drug uses. Although PRL is a calcium-regulating hormone that stimulates intestinal calcium absorption in lactating rats, whether PRL is capable of stimulating calcium absorption in male rats has been elusive. Herein, the transepithelial calcium transport and electrical characteristics were determined in ex vivo duodenal tissues of male rats by Ussing chamber technique. We found that PRL receptors were abundantly present in the basolateral membrane of the duodenal epithelial cells. PRL (200-800ng/mL) markedly increased the active duodenal calcium transport in a dose-dependent fashion without effect on the transepithelial resistance. The PRL-enhanced active duodenal calcium transport was completely abolished by L-type calcium channel blocker (nifedipine) as well as inhibitors of the major basolateral calcium transporters, namely plasma membrane Ca2+-ATPase and Na+/Ca2+exchanger. Several intracellular mediators, such as JAK2, MEK, PI3K and Src kinase, were involved in the PRL-enhanced transcellular calcium transport. Moreover, PRL also stimulated the paracellular calcium transport in the duodenum of male rats in a PI3K-dependent manner. In conclusion, PRL appeared to be a calcium-regulating hormone in male rats by enhancing the L-type calcium channel-mediated transcellular and the paracellular passive duodenal calcium transport. This phenomenon could help restrict or alleviate negative calcium balance and osteoporosis that often accompany hyperprolactinemia in male patients. © 2012 Elsevier Inc.